KETERAMPILAN GURU DALAM PENGELOLAAN KELAS - Maryanto Maryanto; Suklani Suklani (CV. ADIBA AISHA AMIRA, 2023)
Education is the main key to the formation of human resources which is a component in building the nation. Education has a very urgent role to ensure the development and continuity of the life of a nation. Education is also a benchmark for advancing a nation, and a reflection of people's personality. Competencies that must be possessed by an Islamic religious education teacher like other teachers include: Pedagogic competence, personal competence, professional competence, social competence. This study aims to determine 1) The role of Islamic Religious Education in increasing student learning motivation. 2) To find out the supporters of student motivation in studying Islamic education. This research is a type of literary research, namely research that uses literature (books) as a reference material. The methods used in this study are: 1) Inductive method, this method uses ways of thinking from things that are specific to things that are general in nature. 2) The deductive method, this method uses ways of thinking from general things to specific things. 3) Correlation Method, this method uses ways of thinking by looking for correlations (relationships) between one thing and another.